离散饮食 ：在新加坡的马来西亚华人特色美食 = Diasporic food : Malaysian Chinese food in Singapore - 曾佩诗 Chen, Pey Shy (2012)
新加坡的马来西亚特色餐馆日益增加，从马来西亚‘移居’到新加坡，成为了‘离散饮食’。每年有大批的马来西亚华人到新加坡读书和工作，长期定居在本地。马来西亚华人群体不断扩大，也把属于自家乡的特色饮食也带到本地。研究显示，本来本地的马来西亚饮食是马拉西亚华人消解乡愁的途径，却发现在本地的马来西亚特色菜的服务对象从在本地的马来西亚华人，转向了新加坡华人社群。在现代化和跨国性的的语境下，马来西亚特色菜不仅成为了新加坡饮食文化的一部分，也已‘离散饮食’的身份到客居国，得到了认可。本文考察新加坡华人和马来西亚华人的观点，进一步探讨马来西亚特色饮食在新加坡的接受度。 Every year, a large number of Malaysian Chinese stay in Singapore for long term studies and work. As this group of Malaysian Chinese increases in size, they are in need of a way to relief nostalgia, providing a support for the Malaysian Chinese in Singapore. This results in the tremendous hike in the number of Malaysian Chinese food in Singapore. Being a diasporic individual, Malaysian Chinese food migrates to Singapore, away from its homeland. This thesis finds that instead of the Malaysian Chinese as the main audience for Malaysian Chinese food in Singapore, it has shifted its focus towards the Singaporean Chinese. In this modern and transnational society, Malaysian Chinese food has not only been just a diasporic individual amongst the diverse food culture in Singapore, but has since been accepted as part of the culture.